Comparison of Ultrasound-Guided Transversus Abdominis Plane Block with Bupivacaine and Ropivacaine as Adjuncts for Postoperative Analgesia in Laparoscopic Cholecystectomies - Vaibhav, Vivek (Academia Anesthesiologica International, 2020)
Background: To compare ultrasound-guided transversus abdominis plane block with bupivacaine and ropivacaine as adjuncts for postoperative analgesia in laparoscopic cholecystectomies. Subjects and Methods: 76 patients scheduled for laparoscopic cholecystectomy, were split into 2 groups of 38 each. Both groups got ultrasound-guided TAP blocks with 0.25% bupivacaine (plain) in group I and 0.375% ropivacaine (plain) in group II. At time intervals of 10 minutes, 30 minutes, an hour, four hours, eight hours, twelve hours, and twenty-four hours, all patients were evaluated for post-operative pain and rescue analgesic usage. Results: Group I had 20 males and 18 females and group II had 17 males and 21 females. The mean weight in group I was 64.2 kgs and in group II was 63.8 Kgs. The mean height was 158.4 cms in group I and 158.3 cms in group II. The mean duration of surgery was 71.4 minutes in group I and 74.2 minutes in group II. The difference was non- significant (P> 0.05). The mean pain score at 10 minutes was 0.0 in both groups. At 30 minutes, it was 1.6 in group I and 0.0 in group II. At 1 hour was 2.0 in group I and 0.0 in group II. At 4 hours was 2.4 in group I and 2.5 in group II. At 8 hours was 2.2 in group I and 2.3 in group II. At 12 hours was 1.6 in group I and 2.1 in group II. At 24 hours was 1.2 in group I and 1.1 in group II. The difference was significant (P< 0.05). Conclusion: In patients undergoing laparoscopic cholecystectomy, ultrasound-guided deposition of ropivacaine 0.375% in the TAP offered greater analgesia in the early post-operative period compared to bupivacaine 0.25%.